Few-layer phosphorene: An emerging electrode material for electrochemical energy storage. (June 2019) - Tao, Yaping; Huang, Ting; Ding, Chunxia; Yu, Feng; Tan, Deming; Wang, Faxing; Xie, Qingji; Yao, Shouzhuo
Graphical abstract: A comprehensive summary on few-layer phosphorene as electrode materials for electrochemical energy storage systems is provided in this review. Highlights: The review introduces the phosphorene electrodes for batteries and supercapacitors. Future possibilities and opportunities of phosphorene electrodes are suggested. The key challenges of phosphorene electrodes are provided in this thriving field. Abstract: The emergence of phosphorene in 2014 augments the family of two-dimensional (2D) materials, which soon triggered tremendous interest in the field of physics, chemistry, biomedicine, and materials science. Considering the tunable band gap, large interlayer spacing (0.53 nm), high charge carrier mobility and strong in-plane anisotropy, tremendous research efforts have been dedicated to the exploration of phosphorene's applications in electrochemical energy storage systems. This review, both theoretically and experimentally, introduces the state-of-the-art development of few-layer phosphorene as the electrode material for electrochemical energy storage systems. The discussed electrochemical energy storage systems involve Li-ion batteries, Na-ion batteries, K-ion batteries, Li-S batteries and supercapacitors. More importantly, perspectives on future possibilities and opportunities of electrochemical energy storage devices based on few-layer phosphorene are also suggested, including dual-ion batteries and metal-ion hybrid capacitors. Finally, the key challenges of phosphorene electrodes are provided for the further research in this thriving field.